MENINGKATKAN KEMAMPUAN MENULIS NARASI SISWA KELAS V MELALUI MODEL KOOPERATIF TGT DI SDN 20 KAMPUNG BARU - Desrini Darma Putri; Sisri Wahyuni; Riri Marfilinda (LP2M Universitas Adzkia, 2025)
The low level of student learning activity in writing narrative essays in the Indonesian language subject at the fifth grade of SDN 20 Kampung Baru, Pesisir Selatan Regency, formed the background of this study. Identified problems included students' tendency to play during lessons and a lack of participation in discussions. Therefore, this study aimed to describe the improvement of students' narrative writing activities through the application of the Teams Games Tournament (TGT) cooperative model. This study utilized a qualitative approach with classroom action research (CAR) consisting of planning, implementation, observation, and reflection, conducted over two cycles. The subjects were the fifth-grade students and teacher. Data were collected through observation, tests, and interviews. The results indicated a significant increase in oral activity (from 69% to 82%), listening activity (from 68% to 83%), and writing activity (from 67% to 82%). Thus, it is concluded that the TGT model is effective in improving student activity in writing narrative essays.